Higher S-adenosylhomocysteine and lower ratio of S-adenosylmethionine to S-adenosylhomocysteine were more closely associated with increased risk of subclinical atherosclerosis than homocysteine - Xiao, Jinghe; You, Yiran; Chen, Xu; Tang, Yi; Chen, Yuming; Liu, Qiannan; Liu, Zhaomin; Ling, Wenhua (Frontiers in Nutrition, 2022)
Aim: To examine the relationship of C1 metabolites of methionine cycle with the risk of subclinical atherosclerosis (SA) in Chinese population. Methods: Total 2991 participants aged 45-75y were included for data analyses based on the baseline data of Guangzhou Nutrition & Health Cohort. Three core serum methionine metabolites including serum S-adenosylmethionine (SAM), S-adenosylhomocysteine (SAH), and homocysteine (Hcy) were measured by UPLC-MS/MS. SA was determined by B-mode ultrasound measured carotid intima-media thickness (CIMT) at the common artery and bifurcation segments. Multivariable logistic and linear regression models were performed to estimate the associations of C1 metabolites of methionine cycle with SA risk or CIMT. After controlling for potential cofounders and other C1 metabolites, in comparison with the lowest quartile, participants in the highest quartile had lowed risk of SA by 27.6% (OR=0.724; 95% CI: 0.563-0.930, Ptrend=0.007) for SAM and 32.2% (OR=0.678; 95% CI: 0.538-0.855, Ptrend<0.001) for SAM/SAH, while increased SA risk by 27.9% (OR=1.279; 95% CI: 1.065-1.535, Ptrend<0.001) for SAH. No significant association was observed for Hcy with SA after further adjustment of SAH and SAM. The results of multivariable linear regression showed similar findings. The highest two standardized coefficients were observed for SAH (β=0.104 for CCA and 0.121 for BIF, P<0.001) and SAM/SAH (β=-0.071 for CCA and -0.084 for BIF, P<0.001). Subgroup analyses suggested more evident associations of SAH with SA were observed in participants of higher cardiovascular risk profiles. Conclusion: Our cross-sectional data showed higher serum SAH but lower SAM/SAH were independently associated with increased risk of SA among Chinese middle-aged and elderly population.